Produtividade e controle de podridão radicular na cultura da mandioca (Manihot esculenta) com o uso de Trichoderma spp - Stefanello, Luciano (2016)
Cassava culture has great importance for agriculture and for populations mainly those in development, for being a culture with high rusticity and productivity, but diseases have been reducing the productivity and invalidating croplands, as in the case of root rot. Therefore the aim of this study was to investigate the potential of Trichoderma to control root rot in cassava caused by Fusarium and Phytophthora, and to investigate the ability of Trichoderma to promote the development of culture and the use of Trichoderma combined with different varieties in both systems. Initially in vitro tests were performed with 23 isolates of Trichoderma spp., the pair of test cultures, production of volatile and non-volatile antimicrobial compounds, against Phytophthora drechsleri development and Fusarium solani, under field conditions cassava planting was realized using the range Fécula Branca in conventional system where at planting was performed spraying spore suspension six of Trichoderma isolates on cuttings in the planting furrow. A second experiment was performed in two culture systems with two varieties with and without Trichoderma harzianum application. For nonvolatiles antimicrobial compounds the isolate studied presented a high ability to reduce mycelial growth of P. drechsleri and F. solani with inibiting up to 100%, to evaluate nonvolatiles antimicrobial compounds produced by Trichoderma the results were less expressive with the maximum inhibition value of 23,87%. for the first experiment under field conditions,the isolated TLB 14 promoted a better root development, consequently providing more productivity, for the incidence of disease the isolates TOD2A, TLB14 and TI2 presented lower incidence. for the second experiment under field conditions, about the plant stand it was lower in range Baianinha and using T. harzianum, the incidence of brown streak was lower in conventional tillage and the productivity was higher in convencional tillage and using T. harzianum